Effects of Cr alloying on the evolution of solidification microstructure and phase transformations of high-Nb containing γ-TiAl based alloys. (April 2021) - Singh, Vajinder; Mondal, Chandan; Sarkar, Rajdeep; Bhattacharjee, P.P.; Ghosal, P.
Abstract: Evolution of the as-solidified microstructures of Ti–45Al–8Nb, Ti–45Al–8Nb–2Cr-0.2B, Ti–45Al–8Nb–4Cr-0.2B alloys, and phase stability during high-temperature exposure (1000°, 1100°, 1200 °C) have been analyzed in the present report. Macroscopic examinations of the as-cast pancakes indicate that Nb, Cr, and B alloying can be effectively utilized as potential grain/colony size refiners for Ti–45Al base TiAl alloys. However, the as-cast microstructure varies considerably from a nearly fully lamellar (α2 +γ) structure for 0 at.% Cr to a dominant coarse-γ laths+β(B2) structure for 4 at.% Cr addition to the baseline Ti–45Al–8Nb alloy. Examination of characteristics of prior-β dendritic morphology and associated crystallographic considerations and surface relief effects establish that all the alloys studied here solidify through the β-phase field. No peritectic α formation could be established. Formation of γ within β phase and lamellar microstructures are attributed to the reactions β→β+γ, and α→α2 +γ, respectively in the as-cast condition. It has been established that strong Cr partitioning in the β-phase significantly slows down the kinetics of β-phase decomposition into γ, and σ. This causes departure from the evolution of phases as predicted by thermodynamic calculations. The solidification microstructure resulting from the solid-state phase transformations are further discussed in terms of the micro-segregation and crystallographic characteristics of the parent and the product phases. Highlights: Cr addition to the high Nb-containing γ-TiAl alloy significantly alters the microstructure and constituent phases. Strong Cr partitioning in β-phase leads to its increased stability. Apparent deviation of transformation pathway is caused by sluggish kinetics of β-decomposition with increasing Cr content. Prominent β-segregation patterns control the spatial distribution of microstructural constituents. Crystallographic analyses of phase interface highlight the salient features of variant selection of transformation products.